Grammar rules-like as developing the practical direction of linguistics - Khamidova Zarina Khomidovna (International Journal on Orange Technologies, 2020)
Through the content of linguistics,it has been important to activate cognitive activity.Competence restructuring of the basic of linguistics is a requirement of time for improving the content of education.This article provides feedback on the availability of a number of objective and subjective factors to make teaching grammatic materials an important tool for enhancing student learning.